Commutativity results and Continuity of Jordan homomorphism on Banach algebras - Zivari-Kazempour, Abbas (Global Journal of Mathematical Analysis, 2014)
In this paper we give conditions which entailing the commutativity of Banach algebra A and then we show that under special hypotheses, each Jordan homomorpishm between Banach algebra A and B is continuous. Keywords: Jordan homomorphism, ring homomorphism, commutative.